A gradient activation method for direct methanol fuel cells. (15th April 2017) - Liu, Guicheng; Yang, Zhaoyi; Halim, Martin; Li, Xinyang; Wang, Manxiang; Kim, Ji Young; Mei, Qiwen; Wang, Xindong; Lee, Joong Kee
Highlights: A gradient activation method was reported firstly for direct methanol fuel cells. The activity recovery of Pt-based catalyst was introduced into the novel activation process. The new activation method led to prominent enhancement of DMFC performance. DMFC performance was improved with the novel activation step by step within 7.5 h. Abstract: To realize gradient activation effect and recover catalytic activity of catalyst in a short time, a gradient activation method has firstly been proposed for enhancing discharge performance and perfecting activation mechanism of the direct methanol fuel cell (DMFC). This method includes four steps, i.e. proton activation, activity recovery activation, H2 -O2 mode activation and forced discharging activation. The results prove that the proposed method has gradually realized replenishment of water and protons, recovery of catalytic activity of catalyst, establishment of transfer channels for electrons, protons, and oxygen, and optimization of anode catalyst layer for methanol transfer in turn. Along with the novel activation process going on, the DMFC discharge performance has been improved, step by step, to more than 1.9 times higher than that of the original one within 7.5 h. This method provides a practicable activation way for the real application of single DMFCs and stacks.